Gender perspective on the global compact for safe, orderly and regular migration - Nikolić, Ivana (Sociološki pregled, 2022)
This paper is dedicated to the gender analysis of the Global Compact on safe, orderly and regular migration since 2018. In the past 30 years, research within migration has also included an analysis of gender and gender inequalities. The inclusion of gender and the principles of gender responsibility in the Compact indicates the determination of the states to include the experiences of women and men in their legal systems. The paper raises questions such as whether gender is integrated into the Compact and, if so, in what way, and what positive and negative effects it will have on the migration of women. The lack of gender analysis through all the principles and goals of the Compact indicates outdated understanding of gender. Such perspectives do not create a fundamental change at the state level. This paper will point out the current as well as future impacts of the Compact on women and men in the process of global mobility. The work of the International Migration Network and the reports of the countries on the implementation will be taken into account, with an additional element of the current Coronavirus pandemic and its impact on the implementation.